2019 IEEE International Ultrasonics Symposium (IUS) 2019
DOI: 10.1109/ultsym.2019.8926023
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Capacitive Micromachined Ultrasonic Transducers for the detection of proton-induced thermoacoustic waves

Abstract: This study investigates the application of broadband capacitive micromachined ultrasonic transducers (CMUT) to ionoacoustics (i.e., the thermoacoustic emissions induced by the energy deposition of ion beam) over a wide frequency range from hundreds of kHz to a few MHz. A water tank was irradiated by a 20 MeV pulsed proton beam. The frequency and amplitude of the ionoacoustic waves were modulated by adding material before to penetrate into the water tank to change the beam energy and its spatial dimensions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The integrated front-end electronic was designed to operate in the 40 kHz to 15 MHz range in reception. We previously showed that the broadband capability of this detector allows to effectively measure ionoacoustic signals in the investigated frequency range without signal distortion induced by the sensor frequency response 30 . This unique feature motivated the choice of the CMUT probe for the experiments as it ensures a proper detection of both the kHz and MHz signals, as required by the measurements with ripple filter, whereas conventional piezo-composite-based transducers, typically characterized by narrower bandwidths, would have only captured one range of frequencies.…”
Section: Ionoacoustic Measurementsmentioning
confidence: 99%
“…The integrated front-end electronic was designed to operate in the 40 kHz to 15 MHz range in reception. We previously showed that the broadband capability of this detector allows to effectively measure ionoacoustic signals in the investigated frequency range without signal distortion induced by the sensor frequency response 30 . This unique feature motivated the choice of the CMUT probe for the experiments as it ensures a proper detection of both the kHz and MHz signals, as required by the measurements with ripple filter, whereas conventional piezo-composite-based transducers, typically characterized by narrower bandwidths, would have only captured one range of frequencies.…”
Section: Ionoacoustic Measurementsmentioning
confidence: 99%
“…[1][2][3] In contrast to nuclear-interaction-based techniques, such as prompt gamma detection and positron emission tomography, ionoacoustics can use detectors as compact as several centimeters or millimeters. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Therefore, it is easier to use with imaging modalities such as x-ray fluoroscopy 19 and MRI scanners 20 deployed close to patients. Additionally, ionoacoustics has an advantage in conjunction with high-dose-rate irradiation, which is being investigated in the context of FLASH, as the acoustic pressure signal is increased at a high beam current.…”
Section: Introductionmentioning
confidence: 99%
“…Ionoacoustics, or protoacoustics, is a promising approach that is used to recover dose conformity by identifying the beam range or reconstructing the dose distribution in real time via the detection of the thermoacoustic waveform emitted from the region of dose deposition 1–3 . In contrast to nuclear‐interaction‐based techniques, such as prompt gamma detection and positron emission tomography, ionoacoustics can use detectors as compact as several centimeters or millimeters 4–18 . Therefore, it is easier to use with imaging modalities such as x‐ray fluoroscopy 19 and MRI scanners 20 deployed close to patients.…”
Section: Introductionmentioning
confidence: 99%
“…In these ideal conditions, the initial pressure reaches its maximum at the BP position, where the dose is maximum as well. As a result, positioning an acoustic detector along the proton beam axis, distal to the BP, allows to verify the proton beam range in the medium by a timeof-flight analysis, whereas the initial pressure distribution can be reconstructed using multiple sensors [7], both requiring the use of broadband detection system to accurately capture the shape of the ionoacoustic signal in which the information of the dose is imprinted [8]. This study investigates the use of a 28 µm-thick PVDF detector, operating at frequencies much lower than its thickness-mode resonance frequency (34 MHz in air), enabling the broadband detection of low-pressure (≤ 0.1 Pa) and low-frequency (≤ 100 kHz) ionoacoustic signals at clinically relevant dose [9].…”
Section: Introductionmentioning
confidence: 99%